Development of Pedagogical Interaction of Penitentiary Workers (1980-2000) - Dermontas, Julius (Acta Paedagogica Vilnensia, 2001)
The problem of the pedagogical interaction between the penitentiary workers and the inmates is a topical issue in Lithuania today. The essence of the constructive interaction is empathy, and the aim of the interaction is to create and make the members of the interaction more cooperative with each other. The opposite effect to that of the interaction brings about unnatural and abnormal behaviour both of the trainers and their trainees. The aim of the a11icle is to set the peculiarities of the interaction between the workers of the penitentiary institutions and the inmates, and to look at the perspectives of improving their penitentiary activities and pedagogical interaction. The research has demonstrated that if the needs of an inmate personality are satisfied by work and production it helps to enhance the human interrelation between the workers and inmates of the penitentiary institutions as well as encourage the sentenced persons to reform and to behave morally. The suggested hypothesis has been proved. Such a precondition is essential in improving the pedagogical process of the penitentiary institutions and guaranteeing the public safety and prevention of crime. A possibility for the inmates to satisfy their needs by decent work ( at present only 22 per cent of the sentenced people have work) would create natural conditions for them to improve, as well as make the human relations better and decrease the number of criminal offences. The assumption that the relation between the Workers of the penitentiary system and the inmates is empathic has not proved. Up to 1990 - the year of the Declaration of Independence of Lithuania - there was no a correlative relation between the workers of the penitentiary institutions and inmates. Therefore the impersonal interaction without any empathy predominated. This has resulted in aggressiveness. In order to improve the pedagogical interaction, the psychological and pedagogical qualification of the penitentiary system workers should be raised. On the grounds that this particular kind of interrelation is based upon the laws, the primary nee d is to establish a more effective legal basis for correctional process a11cl to use the experience of foreign countries in this sphere. The study has shown that the present situation calls for Correctional or Penitentiary Code instead of the Executive Code. It is also urgent to pass from the penal to rational social policy and solve people's persona] problems. In the process of humanizing the penal policy, alternative means of punishment, i.e. restorative justice and probation and parole are applied. An article ensuring that all sentenced persons (except for the extremely dangerous) who have served two thirds of the punishment are sent without trial to parole institutions should be included in the Correctional Code.
Keywords: Pedagogical interaction; penitentiary system; penitentiary institutions.